A comparison of co-regulation policies in the perishable food supply chain of India and China: an empirical approach. Issue 3 (24th March 2020) - Rais, Mohammad; Kaul, Arshia; Jain, Akansha
Although food safety has become an important concern nowadays, yet public sector enterprises sometimes face difficulties in providing the final items in the required quantity and at the desired quality levels. Here, we consider the aspect of co-regulation in handling the food quality in the fruits and vegetables sector from farm to fork stage of the perishable food supply chain in India and China. The aspects considered in this paper are: current status of the perishable food supply chain in the two countries, analysis of the level of incorporation of co-regulation in the policies of the respective countries, evaluation of the role of co-regulation in enhancing the perishable food supply chain and analysis of limitations of the current policies and steps to be implemented for improvement in the future. The authors have been able to identify the varying policies of co-regulations in the two countries.